Warming up using electrical muscle stimulation - does it increase strength and power? - Ng, Jonas Jun Wei (2019)
Background – Time cost of exercise constitutes a major barrier to participation. Electrical muscle stimulation (EMS) has been documented to recruit fast-twitch muscle fibres quicker, potentially reducing warm-up duration for strength and power movements. However, few studies have explored EMS in warm-ups. Purpose – The purpose of this study was to compare acute strength, power and time to first maximal attempt of back squats and barbell calf-raises between EMS warm-up and traditional incremental loading. Methods – A within-subjects, counterbalanced randomized crossover design was adopted. Seventeen male participants experienced in both motions underwent two main sessions in randomized order: EMS warm-up and Traditional warm-up. Each session entailed performing either warm-up followed by three attempts at One Repetition Maximum (1RM) back squat, before performing the same type of warm-up followed by three attempts at Ten Repetition Maximum (10RM) barbell calf-raise. Load and maximum power during heaviest successful attempt, along with time taken to first maximal attempt, for each motion were measured via force platform and stopwatch. Paired samples t-test and Wilcoxon’s signed rank test were used to compare for differences between warm-ups. Results – Strength and power showed no significant differences between the two warm-ups conditions (p > 0.05). Time to first 1RM back squat showed no significant difference (p > 0.05), whereas time to 10RM calf-raise was significantly higher in EMS warm-ups than traditional (p = 0.008). Conclusion – EMS warm-up is an equivalent substitute of traditional incremental loading, though its benefits to time and power diminishes with multiple applications per session.